PENERAPAN STRATEGIPEMBELAJARAN AKTIF TIPEFIRING LINE DISERTAI HANDOUT UNTUK MENINGKATKAN AKTIVITAS DAN PEMAHAMAN KONSEPMATEMATIS SISWAKELASVIIISMPN 1 IV JURAI KABUPATEN PESISIR SELATAN - Putri, Lisa Erdina Media; Edriati, Sofia; Cesaria, Anna (STKIP PGRI Sumbar, 2013)
This research was stimulated by the backgraund of lower studentsâ activity in learning mathematic and their comprehension about the math concept at the class VIII SMPN I IV Jurai of South Pesisir Was Still Lower. The objective of this research are: 1) to know whatever the studentsâ teaching activity by using active teaching strategy of Firing Line Tipe provided with Handout. 2) To Know whatever the studentsâ comprehension of math concepety by using active teaching stategy of Firing Line type provided with Handout was better than studentsâ comprehension of math by using conventional teaching. The type of this research was experimental research was all students at the class VIII SMPN I IV Jurai of South Pesisir period 2013/2014 consisted four classes. Technique of taking sample was done randomly by selecting the class was VIII4 as exsperimental class and VIII2 control class. This research used intrument of observation sheets and studentsâ comprehension of mathematic concept test. This formh of test used essay by reliability test score R11=0,91. Based on the observation result can be concluded that the implementation of active teaching strategy of Firing Line type provided with Handout can improve studentsâ activity in teaching, especially students Y who work yhe problem from students X have increased from 83% become 95%. The result of hypothesis by using t-test was obtained p-value = 0,002 less than Â = 0.05. Thus the hypothes in this research was accepted with the confidence level 95%. Therefore can be concluded that the studentsâ comprehension about mathematic concept by using active teaching strategy of Firing Line type provided with Handout was better than studentsâ comprehension of math concept by using conventional teaching model toward student at the class VIII SMPN I IV Jurai of South Pesisir.